Penyuluhan Dan Pelaksanaan Go Green Di Desa Citaleus, Kecamatan Buahdua, Kabupaten Sumedang - Raizal Fahmi; Sri Wilujeng; Reni Srimulyaningsih; Ina Darliana; Ishak Tan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The solution that can be applied to the community to deal with the impact of global warming today is the concept of